Urban Farming: Implementation of Government Policy on Food Security and Community Quality of Life Programs - Ahmad Choirul Fathihin; Lailul Mursyidah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The implementation of the urban farming program is a form of the Sidoarjo regency government's efforts to support food security and improve the quality of life of people in densely populated areas and on the other hand Sidoarjo has experienced a conversion of agricultural land to housing and factories. This program aims to enable people to meet their food needs independently and improve the economy and motivate them to form farmer groups to build themselves to be more independent and develop. The background of this study is based on the results of the researcher's initial observations looking at the problem of agricultural land conversion due to the high population surge and infrastructure development in Sidoarjo Regency which interferes with food conditions and the quality of life of the community. Therefore, this study wants to know how the implementation of the urban farming program in supporting food security and improving the quality of life of the people in Sidoarjo regency. In this study, researchers used qualitative methods with a descriptive approach. Data collection is carried out with interview techniques, observation, and documentation. Drawing conclusions related to the reality in the field regarding the implementation process of the urban farming program in Taman Pinang Housing, Lemahputro Village, Sidoarjo Regency.